ANALISIS GOOD CORPORATE GOVERNANCE DALAM PENINGKATAN KINERJA PERUSAHAAN (STUDI KASUS PADA HOTEL ASIDA) - Putri, Riska Ameliya (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2018)
This research purpose is to find out aplication of good corporate governance in pursuing of performance improvement at hotel asida business. Good corporate gorvenance aim to prevent and fix significant mistakes.This research is a qualitative research with descriptive approach. The research method is interview to manager, hotel staff, and document analyst, also using secondary data which is financial report in the year of 2015-2016.Analysis result shows that good corporate governance could improve performance at hotel asida. Application of transparancy principle could be improved by creating hotel webpage, so it can helps improving of administration performance. Furthermore, it can helps in improving of room occupancy and improving operational hotel performance that affect creditor trust, so hotel asida can reduce financing fund. This can help employee productivity improvement, so operational performance is increasing.